Penerapan Pidana Terhadap Pelaku Penangkpan Ikan Menggunakan Bahan Peledak - Samalelaway, Hendry Piter; Wadjo, Hadibah Zachra; Leasa, Elias Zadrach (Faculty of Law Universitas Pattimura, 2025)
The purpose of this study is to determine and analyze the legal considerations and deterrent effects on those who are given a criminal sentence of less than 1 year for fishing using explosives or fish bombing. Fish bombing is the use of explosives to produce an explosion that releases large and fast energy in a fishing area in order to kill fish, making it easier for the bomber to catch fish. The use of bombs in fishing causes damage to marine resources and the environment, especially coral reef ecosystems. This writing uses a Normative Juridical research type, with a statutory regulatory approach, a conceptual approach and a case approach. The problem that the author can discuss is the Judge's Legal Consideration in Imposing a Criminal Sentence of One Year. Based on the provisions of Law Number 45 of 2009 amending Law Number 31 of 2004 concerning Fisheries. There are several types of crimes in fisheries that are contained in Articles 84 to 101. The results of the study show that the act of fishing using explosives carried out by perpetrators who are given criminal sanctions of less than one year is not in accordance with existing laws, as can be seen in Article 84 paragraph (1)